The Effects of Livelihood Risk on Poverty Types among Smallholder Cassava Farmers in Anambra State, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2024)
This study investigates the poverty types experienced by smallholder cassava farmers in Anambra State, Nigeria, utilizing the international poverty line of $2.15 per day as updated by the World Bank in 2022. The data for the study was collected from a random sampling of 168 farmers after which 150 (89.3%) were found usable. The analytical techniques used for the analysis include descriptive statistics, mean threshold of 5-point Likert scale, ordinal, and multinomial logistics regression analysis. Findings reveal that 74.0% of the farmers live in absolute poverty, with monthly incomes below $451.50, necessary for basic needs. Additionally, 24.0% are relatively poor, earning below $62.30 per month, indicating significant income inequality. Only 2.0% of farmers earn above this threshold, underscoring the critical economic challenges faced by the majority. The analysis of livelihood risks using a 5-point Likert scale shows significant health, environmental, financial, and social risks affecting these farmers. Health risks like illness and poor healthcare access, environmental risks such as extreme weather and soil erosion, and financial constraints including limited access to funds are prominent. Social insecurity also exacerbates these issues. An ordinal logistic regression analysis indicates that health, environmental, financial, and social risks significantly influence poverty levels. Key socioeconomic factors such as age, marital status, farming experience, education, and household size also play crucial roles. The study emphasizes the need for targeted interventions to address these risks, promote sustainable agricultural practices, and improve access to education and financial services to alleviate poverty among these farmers.
Keywords: Cassava farmers; Livelihood; Poverty line; Relative poverty; Smallholders